The Impact of Non-Thyroidal Illness Syndromes on The Prognosis and Immune Profile in Severe Fever with Thrombocytopenia Syndrome Patients - Wu H; Mu Y; Liu Y; Zhang R; Xu Y; Zhang Y; Zhao C; Zhang W; Lin L; Chen Z (Infection and Drug Resistance)
Hongxiao Wu,1– 3,* Yameng Mu,1– 3,* Yuanni Liu,4 Ruihua Zhang,1– 3 Yanli Xu,4 Yuanyuan Zhang,1– 3,5 Chenxi Zhao,1– 3 Wei Zhang,1– 3 Ling Lin,4 Zhihai Chen1– 3 1National Key Laboratory of Intelligent Tracking and Forecasting for Infectious Diseases, Beijing Ditan Hospital, Capital Medical University, Beijing, People’s Republic of China; 2Beijing Key Laboratory of Emerging Infectious Diseases, Institute of Infectious Diseases, Beijing Ditan Hospital, Capital Medical University, Beijing, 100015, People’s Republic of China; 3National Center for Infectious Diseases, Beijing Ditan Hospital, Capital Medical University, Beijing, 100015, People’s Republic of China; 4Department of Infectious Diseases, Yantai Qishan Hospital, Yantai, People’s Republic of China; 5Beijing Institute of Infectious Diseases, Beijing, 100015, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhihai Chen, Department of Infectious Disease, Beijing Ditan Hospital, Capital Medical University, 8 Jingshun East Street, Chaoyang District, Beijing, 100015, People’s Republic of China, Email Chenzhihai0001@126.com Ling Lin, Department of Infectious Diseases, Yantai Qishan Hospital, Yantai, People’s Republic of China, Email linling4012@163.comBackground: Non-thyroidal illness syndrome (NTIS) is the most common endocrine dysfunction in critically ill patients and is often associated with poor prognosis. Thyroid dysfunction and immune cell disturbances are frequently observed in patients with severe fever with thrombocytopenia syndrome (SFTS). This study aims to evaluate the impact of NTIS on the prognosis of SFTS patients and to explore the relationship between thyroid hormones (THs) and immune cell profiles.Methods: Adult patients admitted to Yantai Qishan Hospital for SFTS from January 2023 to December 2023 with no prior history of thyroid disease were retrospectively recruited. Multivariable regressions were used to assess the associations between NTIS and clinical outcomes. Spearman correlation analysis was conducted to evaluate the relationships between immune cells and THs. SFTS patients with NTIS were categorized into four subtypes based on different levels of FT4 and TSH, and the association between NTIS subtypes and mortality was further analyzed.Results: Of the 84 SFTS patients included in the study, 62 (73.8%) were diagnosed with NTIS. Independent risk predictors which may affect prognosis of SFTS patients include NTIS subtype (P =0.002), viral load (P = 0.029), FT3 (P = 0.032), and FT4 (P = 0.041). SFTS patients with NTIS exhibited a higher mortality rate compared to euthyroid patients (P = 0.033). Spearman correlation analysis revealed that LYM, LYM%, MONO, MONO%, BAS, CD3+T, CD3+T%, Th, and Th% were positively correlated with FT3, FT4, or TSH levels. NTIS patients were more likely to present with coagulation abnormalities (APTT, P = 0.005; D-Dimer, P < 0.001), liver enzyme abnormalities (AST, P = 0.001), electrolyte imbalances (Sodium, P = 0.003), elevated LDH (P = 0.001), and increased ɑ-HBDH (P = 0.003).Conclusion: NTIS is common in SFTS patients, and SFTS patients with NTIS have a lower survival rate compared to euthyroid patients. The mortality risk in NTIS type 3 patients is higher than in those with NTIS type 1.Keywords: SFTS, non-thyroidal illness syndrome, thyroid dysfunction, immune cells